GC-MS and molecular docking analysis of Kodo millet (Paspalum scrobiculatum) identifying the compounds with anti-diabetic potential - Natesan, Senthil; Louis, Infant Richard Joseph; Balan, Suganya; Mallaian, Vaithiyalingan; Periasamy, Meenakshi; Nallusamy, Saranya; Adhimoolam, Karthikeyan (Current Botany, 2023)
Kodo millet (Paspalum scrobiculatum) is a nutritionally superior grain and a rich source of dietary fiber and protein. It helps in managing health and dietary issues such as malnutrition, diabetes, obesity, and celiac disease. Its low content of slowly digestible carbohydrates promotes a gradual release of glucose, helping to maintain stable blood glucose levels. The present study aims to screen and identify phytochemicals in kodo millet and to explore its antidiabetic properties through GC-MS and in silico molecular docking analyses. GC-MS-based metabolomics analysis was conducted to identify a diverse array of metabolites present in four different kodo millet cultivars, yielding 245 metabolites. A GC-MS-based metabolomics analysis identified 245 metabolites across four kodo millet cultivars. Subsequent pathway and enrichment analyses of these metabolites revealed several significantly enriched metabolic pathways, including fatty acid biosynthesis; amino sugar and nucleotide sugar metabolism; cysteine and methionine metabolism; phenylpropanoid biosynthesis; terpenoid backbone biosynthesis; starch and sucrose metabolism; and valine, leucine, and isoleucine biosynthesis. Further investigation into the pharmacological properties of these metabolites, followed by molecular docking analysis against α-amylase, revealed that several compounds possess antidiabetic activity. Collectively, our results demonstrate the basis of kodo millet’s therapeutic potential, adding a layer of health-related significance to its consumption.